2015
DOI: 10.1089/ped.2015.0528
|View full text |Cite
|
Sign up to set email alerts
|

Urine Club Cell 16-kDa Secretory Protein and Childhood Wheezing Illnesses After Lower Respiratory Tract Infections in Infancy

Abstract: Background: Infants with lower respiratory tract infections (LRTIs) are at an increased risk of developing childhood wheezing illnesses (including asthma), but it is not currently possible to predict those at risk for these long-term outcomes. The current objective was to examine whether urine levels of club cell 16-kDa secretory protein (CC16) at the time of an infant LRTI are associated with the development of childhood wheezing illnesses. Methods: Prospective study of 133 previously healthy infants enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Recent developments in high-throughput molecular techniques provide an opportunity for understanding pathogenesis of RSV infection, but a biomarker that accurately and consistently predicts susceptibility to RSV infection, infection severity, and association with subsequent development of persistent wheezing and asthma has yet to be developed (Larkin and Hartert 2015; Openshaw 2013; Rosas-Salazar et al 2015). Metabolic pathways, as a mirror of the interactions between host cell and virus (Pearce and Pearce 2013; Peeples and Levine 1980), provide an opportunity to understand the mechanisms that underlie severe infections and pathways through which RSV ARI contributes to the development of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in high-throughput molecular techniques provide an opportunity for understanding pathogenesis of RSV infection, but a biomarker that accurately and consistently predicts susceptibility to RSV infection, infection severity, and association with subsequent development of persistent wheezing and asthma has yet to be developed (Larkin and Hartert 2015; Openshaw 2013; Rosas-Salazar et al 2015). Metabolic pathways, as a mirror of the interactions between host cell and virus (Pearce and Pearce 2013; Peeples and Levine 1980), provide an opportunity to understand the mechanisms that underlie severe infections and pathways through which RSV ARI contributes to the development of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…The link between its levels and asthma has already been studied, but its relation to acute bronchiolitis has received less attention . We set out to determine whether CC16 could be a severity biomarker of epithelial damage during acute bronchiolitis and of recurrent wheezing in the sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…Zhai and colleagues [66] using human data from a birth cohort, suggested that low circulating CCSP16 levels were not only a biomarker of airway pathology but may be implicated in the pathophysiology of the progressive airway damage that characterize obstructive lung diseases. Moreover, urinary CCSP16 may be a useful tool or biomarker for studying asthma and the integrity of the alveolar epithelium in children with lung injury [69].Emerging biomarkers:…”
Section: 2mentioning
confidence: 99%